2016
DOI: 10.11138/ccmbm/2016.13.2.097
|View full text |Cite
|
Sign up to set email alerts
|

Bone pain mechanism in osteoporosis: a narrative review

Abstract: SummaryBone pain in elderly people dramatically affects their quality of life, with osteoporosis being the leading cause of skeletal related events. Peripheral and central mechanisms are involved in the pathogenesis of the nervous system sensitization. Osteoporosis in the elderly has been associated with increased density of bone sensory nerve fibers and their pathological modifications, together with an over-expression of nociceptors sensitized by the lowering pH due to the osteoclastic activity. The activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…Bone pain mainly occurs due to uncontrolled osteoclastic activity causing altered sympathetic nerve fiber regulation and neuropeptide release. 13,14) Periosteal reaction (<19%), low bone mass (<40%), and fractures (<10%) are consecutive results due to infiltration of leukemic cells in bone. 9)…”
Section: Bone Morbidity At All Diagnosismentioning
confidence: 99%
“…Bone pain mainly occurs due to uncontrolled osteoclastic activity causing altered sympathetic nerve fiber regulation and neuropeptide release. 13,14) Periosteal reaction (<19%), low bone mass (<40%), and fractures (<10%) are consecutive results due to infiltration of leukemic cells in bone. 9)…”
Section: Bone Morbidity At All Diagnosismentioning
confidence: 99%
“…Chronic pain is one of the most important complications of osteoporosis and is a challenging management for clinicians . In addition to the direct effects of resulting fracture which can cause acute and chronic nociceptive and neuropathic pain, pain is also a common feature in osteoporosis without fracture .…”
Section: Cannabinoids and Osteoporotic Painmentioning
confidence: 99%
“…It has been reported that postmenopausal women have significant higher prevalence of low back pain and there is an association of repetitive pain with regional migratory osteoporosis (RMO) . Central sensitization has been suggested to play an important role in the development and maintenance of chronic pain related with osteoporotic fracture which is difficult for treatment and usually requires a comprehensive strategy including a large spectrum of drugs and non‐pharmacological treatments …”
Section: Cannabinoids and Osteoporotic Painmentioning
confidence: 99%
See 2 more Smart Citations